Laparoscopic Radical Excision of Primary Round Ligament Perivascular Epithelioid Cell Tumor Mimicking Leiomyoma - Chailert Phongnarisorn (2018)
Perivascular epithelioid cell tumors (PEComas) are a group of rare mesenchymal tumors including angiomyolipoma, clear cell sugar tumor, lymphangioleiomyomatosis, and other unusual clear cell tumors at various locations. We describe a 45-year-old female patient presenting with a painless mass at the left lower abdomen. Computed tomography showed a circumscribed mass 8 × 7 × 8 cm in the left round ligament of the uterus. The provisional diagnosis was leiomyoma. The patient underwent initial laparoscopic excision. The histological and immunohistochemical diagnosis was malignant PEComa. She subsequently underwent laparoscopic radical excision of the residual left round ligament and surrounding tissue. At 18 months after surgery, she remained well without clinical and radiographic evidence of recurrent disease. According to this report, primary PEComa of the round ligament can mimic leiomyoma. Laparoscopic radical excision might be a feasible and safe alternative treatment of this tumor with a favorable outcome. © 2009 AAGL.